Literature and Identity in the Golden Ass of Apuleius - Graverini, Luca (Book collections on Project MUSE., 2012)
"The second-century CE novel The Golden Ass, or Metamorphoses, has proven to be both captivating and highly entertaining to the modern reader, but the text also presents the critic with a vast array of interpretive possibilities. In fact, there is little consensus among scholars on the fundamental significance of Apuleius' novel: is it simply a form of narrative entertainment, or does it represent some sort of religious or philosophical propaganda? Can it be interpreted as a satire of fatuous belief in otherworldly powers, or is it an utterly aporetic text?"--Publisher's description